2014
DOI: 10.1111/pim.12122
|View full text |Cite
|
Sign up to set email alerts
|

Human filarial Wolbachia lipopeptide directly activates human neutrophils in vitro

Abstract: The host inflammatory response to the Onchocerca volvulus endosymbiont, Wolbachia, is a major contributing factor in the development of chronic pathology in humans (onchocerciasis/river blindness). Recently, the toll-like pattern recognition receptor motif of the major inflammatory ligands of filarial Wolbachia, membrane-associated diacylated lipoproteins, was functionally defined in murine models of pathology, including mediation of neutrophil recruitment to the cornea. However, the extent to which human neut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 38 publications
(55 reference statements)
1
17
0
Order By: Relevance
“…using neutropenic mice also suggested a protective role of neutrophils during the early stage of L. sigmodontis infection53. Wolbachia endosymbionts are known to induce neutrophil activation and accumulation as shown in the in vivo model for ocular onchocerciasis5455, in human onchocerciasis30 and in vitro in which neutrophils are directly activated by human filarial Wolbachia lipoproteins29. Our data supports the hypothesis that Wolbachia derived from incoming L3 larvae provoke neutrophil influx to the skin in a NOD2-dependent manner.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…using neutropenic mice also suggested a protective role of neutrophils during the early stage of L. sigmodontis infection53. Wolbachia endosymbionts are known to induce neutrophil activation and accumulation as shown in the in vivo model for ocular onchocerciasis5455, in human onchocerciasis30 and in vitro in which neutrophils are directly activated by human filarial Wolbachia lipoproteins29. Our data supports the hypothesis that Wolbachia derived from incoming L3 larvae provoke neutrophil influx to the skin in a NOD2-dependent manner.…”
Section: Discussionsupporting
confidence: 83%
“…Human pathogenic nematodes like Onchocerca volvulus , the causative agent of onchocerciasis, or Wuchereria bancrofti , the major cause of lymphatic filariasis, are known to harbor endosymbiotic Wolbachia bacteria (reviewed in refs 25 and 26). Wolbachia are essential for development and survival of their nematode hosts and can induce a pro-inflammatory immune response with strong neutrophil involvement27282930, making them crucial in the pathogenesis of filarial infections3132. It has been shown that these Gram-negative bacteria synthesize lipid II, a peptidoglycan precursor that contains MDP33, suggesting that Wolbachia are a source of NOD2 receptor ligands.…”
mentioning
confidence: 99%
“…In sepsis, E. coli PAL is a potent TLR2 agonist, which contributes to inflammation, cardiac dysfunction, endothelial activation, coagulopathy, and vascular leakage [39][40][41][42]. In filariasis Wolbachia PAL recruits neutrophils, macrophages and other innate immune cells, which accumulate around living Onchocerca adults worms in onchocermata [43,44] and in response to dying microfilariae in the cornea [45,46], which stimulates their activation and the production of an array of pro-inflammatory cytokines and mediators [6,9]. Wolbachia lipoproteins also drive adaptive Th1 immunity through activation of dendritic cells [9].…”
Section: Discussionmentioning
confidence: 99%
“…In sepsis, E. coli PAL is a potent TLR2 agonist, which contributes to inflammation, cardiac dysfunction, endothelial activation, coagulopathy, and vascular leakage [ 39 42 ]. In filariasis Wolbachia PAL recruits neutrophils, macrophages and other innate immune cells, which accumulate around living Onchocerca adults worms in onchocermata [ 43 , 44 ] and in response to dying microfilariae in the cornea [ 45 , 46 ], which stimulates their activation and the production of an array of pro-inflammatory cytokines and mediators [ 6 , 9 ]. Wolbachia lipoproteins also drive adaptive Th1 immunity through activation of dendritic cells [ 9 ].…”
Section: Discussionmentioning
confidence: 99%